(untitled) (IUBAT Review, 2023)
The study was carried out at the Agricultural Research Field of IUBAT to investigate the impact of varying levels of boron (B) fertilizer on the growth and production of okra (Hybrid Okra-Shomy). The experiment followed a Randomized Complete Block Design (RCBD) with four replications. The experiment included four treatments: T0 (Control), T1 (1kg B ha-1), T2 (2kg B ha-1), and T3 (3kg B ha-1). These treatments were implemented in order to assess the optimal outcomes of the study. The findings of the study showed that T2 (2kgB/hac) treatment performed better in all aspects of growing parameter especially yield contributing traits like number of fruit/plant (89.75), number of fruit/treatment (387.98), individual fruit weight (17.34gm), number of seed/fruit (57.50),100 seed weight (8.15gm), yield/plant (387.98gm), yield/hac (1549.7kg), yield (17.09) ton/hac, Plant fresh weight/plant (524.81gm) and root length (20.40cm), respectively. IUBAT Review, 6(2): 106-114